Fabrication of functionally graded bio-inspired microstructures - Nur Azmeer Ikhwan Bin Noremin (Nanyang Technological University, 2023)
This project serves as a study of bio-inspired materials and to fabricate similar functionally graded microstructures and horizontal alignment comparable to that of nacreous shell. It aims to achieve an understanding on the microstructures of the Al2O3 and to perform mechanical tests for evaluation of properties. The application of knowledge from different principles are put into practice in analysing and evaluating the modified configuration of Al2O3 properties. This project will go through the Fabrication of Material, namely Magnetically Assisted Slip Casting and Sintering, and Mechanical Tests such as 3-point bend test and Vickers hardness to analyse Al2O3 while adopting the functionally graded microstructures and horizontal alignment of platelets. Concurrently, this project will inculcate critical thinking and perseverance in implementing such ceramic into real world engineering application.